The Moderating Effect Of Trust On Intention To Use Digital Bank: Technology Acceptance Model (Tam) Approach - Sitompul, Risna Hairani; Lubis, Rini Hayati; Siregar, Rizal Ma'ruf Amidy (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The transition from the traditional world to advanced technology makes banking services easier for digital banks and is supported by an internet network with increasingly easier and broader coverage. The information technology system acceptance model will be used as a Technology or Technology Acceptance Model (TAM). TAM is an individual's intention and attitude to use technology determined by convenience and usefulness. Trust, convenience, and benefits of digital payments influence consumer behavior, especially for Generations Y and Z. The aim of the research that will be carried out is to determine the effect of convenience on intention to use digital banks, the effect of usability on intention to use digital banks, the effect of trust as moderating the effect of ease on intention to use digital banks, the effect of trust as moderating usability on intention to use digital banks. This research was conducted on all students who entered college at UIN SYAHADA Padangsidimpuan in 2020, totaling 162 students with a sample of 115 students. Data is processed using SMARTPLS, version 4. Outer model analysis can be seen from several indicators: Validity Test, Reliability Test, and Multicollinearity Test. Evaluation of the Inner Model: Estimation for Fath Coefficient, R-Square, and Model Fit. Hypothesis Testing Hypothesis testing can be seen from the t-statistic and probability values. The research results show that convenience significantly affects the intention to use digital banks (4,099 1.96). In contrast, the effect of usability, convenience moderated by trust, and the effect of usability moderated by trust on interest in digital bank users are insignificant.